The Foundations of Islamic Finance: Appraising the Approaches and Challenges - Hafas Furqani; Nazaruddin A. Wahid (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2013)
The emergence of Islamic finance as a system of thought and practice is timely in the midst of world crisis and the uncertain proposals for solving it. It is hoped that Islamic finance could offer a coherent perspective for understanding real economic problems as well as a genuine alternative to the very foundations of how finance should be managed to actualize human prosperity. It is widely expected that Islamic finance will continuously evolve into a more sophisticated form and structure in the next decade. Some, however, question whether the development is moving on the right track to realize the hopes pinned on it at the time of its initial establishment. This embarks from the differences in understanding the raison d?etre of Islamic finance emergence and hence approach taken in developing the industry. In this paper we argue that Islamic finance should be directed to provide for meaningful development in thetwenty-first century, Islamic finance must realize its full potential as a system, not merely a stopgap means of surviving the crisis. It must go beyond that to provide the guidelines for managing a good economy, stimulating growth and development, realizing socio-economic justice and promoting employment and stability. It cannot limit itself to merely offering economic and financial practices that satisfy the minimum standard of legal requirements.